Exploring an Ecology of Translation - Marais, Kobus (TTR, 2025)
This paper explores the implications that a biosemiotic theory of translation holds for the debate on ecotranslatology. It considers several current onto-epistemological positions, arguing that some of them are either light on or problematic in their ontology. The paper then considers Kalevi Kull’s four-tier ontology and expands it into a five-tier ontology within which to think about translation and ecology. Relating Kull’s expanded ontology to John Deely’s semiotic realist views, it sets forth a complex onto-epistemology. The paper closes by arguing that translation provides the link between ontology and epistemology as well as between mutually exclusive onto-epistemologies, hence the proposal of a translational ecology.